Pd‐mediated polymerization of diazoacetates with aromatic ester group: Synthesis and photophysical property of poly(1‐pyrenylmethoxycarbonylmethylene). Issue 5 (18th December 2012) - Ihara, Eiji; Okada, Ryoji; Sogai, Takanobu; Asano, Tetsuya; Kida, Masami; Inoue, Kenzo; Itoh, Tomomichi; Shimomoto, Hiroaki; Ishibashi, Yukihide; Asahi, Tsuyoshi
<x xml:space="preserve">Abstract</x> Pd‐mediated polymerization of 1‐pyrenylmethyl diazoacetates affords poly(1‐pyrenylmethoxycarbonylmethylene) (poly4′), whose CC main chain is tightly surrounded by pyrene groups. The intensity ratio of excimer emission to monomer emission (IE/IM) of poly4′ was more than 20 times higher than that of its vinyl polymer counterpart of poly(1‐pyrenylmethyl methacrylate) (polyPyrMA), clearly demonstrating much higher efficiency for excimer formation in poly4′, because of the tight arrangement of the pyrene groups around the main chain. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>